Des acteurs religieux dans la boîte à outils de la politique de lutte contre la radicalisation: aumôniers et médiateurs du fait religieux dans les prisons françaises - Galembert, Claire de (Déviance et société, 2022)
Cooperation with religious personnel in a counter-radicalization policy is still a blind spot in research about this policy in France and elsewhere. While researches are beginning to document the implementation of this policy and provide knowledge about the categories of people who take part in it, little is known about the religious repertoire within this policy that emerged in France since 2014. Based on this observation, this article aims to give a first overview of the association of such actors or religious professionals in relation to this policy in French prisons. The article begins by analyzing the mobilization of religious actors as a resource for public policy at the macro-sociological scale by putting this evolution into perspective both of French conversion to radicalization framing and the transformations of secularism over the last two decades. It shows then at the meso level of the prison, how the invention of the so-called diateurs du fait religieux (literally: "mediators of religious fact")occurred in an incremental way as a result of the disappointments induced by the initial strategy to mobilize Muslim chaplains as bulwarks against extremism. Finally, this article questions the division of religious work between chaplains and the mediators. To conclude one insists on the originality of the religious repertoire in the French anti-radicalization toolkit. If the terrorist context of the 2010s has favored a shift to cooperation with religious personnel, the place given to academic knowledge and to Islamology in this attempt to oppose an ideological response to political violence of Islamic inspiration is no less evocative of the prevalence of the path of dependence linked to the French principles of secularism and separation.